Assessment Of Renewable Energy Sources To Generate Electricity For Remote Areas, South Iraq - Ali Hadi Kother; Zaidoon Waleed AL-Shammari Waleed Jawad; Safaa Kother; Ihsan Ahmed Taha; Hussam Almukhtar; Ahmad Shukri Fazil Rahman; Khairunnisa Hasikin; Muhammad Mokhzaini Azizan (Institute of Advanced Engineering and Science (IAES), 2024)
Indexed by Scopus